Penatalaksanaan Holistik Pada Pasien Hipertensi Derajat II Melalui Pendekatan Kedokteran Keluarga - Zaharuddin, Khairul Husni; Susanto, Tirta Darmawan; Soeryani, Wianti (CV. Jasa Sukses Abadi, 2024)
Hypertension is a global health problem that requires serious attention. Basic Health Research (Riskesdas) in 2018 shows that the prevalence of hypertension in Indonesia with a population of around 260 million is 34.1%, this shows an increase compared to the prevalence of hypertension in Riskesdas in 2013, which was 27.8%. The estimated number of hypertension cases in Indonesia is 63,309,620 people, while the death rate in Indonesia due to hypertension is 427,218 deaths. Data from WHO shows that the number of people suffering from hypertension doubled between 1990 and 2019, from 650 million people to 1.3 billion people worldwide. The purpose of this case report is to explore the role of hypertension management in the context of family medicine holistically and comprehensively through a Patient Centered, Family Focused, and Community Oriented approach. Family medicine has a crucial role in detecting, preventing, and managing hypertension. This study is a case report. Primary data were obtained through autoanamnesis, physical examination, and home visits. Secondary data were obtained from the patient's medical record. Mrs. E, 32 years old, has been complaining of headaches for the past day. Internal risk factors in the patient are being overweight, not exercising regularly, often eating fast food, having a history of cancer in parent, feeling stressed at work, and a curative treatment pattern. External risk factors in the patient is that patient have work activities that are mostly sitting. Diagnosis and management of patient is carried out holistically, Patient Centered, Family Focused, and Community Oriented. There are changes in clinical and patient behavior after the intervention. The family medicine approach emphasizes preventive interventions, patient education, and long-term management. This approach is expected to enhance the understanding of patients and their families regarding the importance of hypertension management and encourage sustainable behavioral changes.